Pediatric Hepatic Abscess in a Resource-Limited Setting: A Case Report - Adinda Paramitha Sukma Damayanti; Khalisah Nurjihany Salsabila; Bethseba Brontang Pulinggomang (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Liver abscess is a rare but serious pediatric infection, more common in developing regions where malnutrition, poor sanitation, and limited healthcare access increase risk. It is broadly classified into pyogenic and amoebic types, with the latter more prevalent in tropical areas. Symptoms such as fever, abdominal pain, and hepatomegaly are often nonspecific, making diagnosis difficult in low-resource settings. Ultrasound plays a crucial role when advanced diagnostics are unavailable. This case illustrates these challenges in a remote hospital in Eastern Indonesia. Case: A 13-year-old boy presented with right upper quadrant pain, intermittent fever, and hepatomegaly. Ultrasound revealed a 7 × 6 cm hepatic abscess. He received empiric intravenous antibiotics, but due to limited facilities for image-guided drainage, exploratory laparotomy with abscess evacuation was performed. The patient showed steady postoperative improvement, was discharged in good condition, and achieved full recovery on follow-up. Discussion: This case illustrates how resource availability influences diagnostic and therapeutic decisions for pediatric liver abscess. Although ultrasound-guided drainage is the preferred minimally invasive approach, the absence of interventional radiology services required surgical management. The patient’s improvement with empiric antibiotics and intraoperative findings supported a pyogenic etiology, underscoring the value of clinical judgment when microbiological testing is unavailable. In settings such as Eastern Indonesia, early imaging and timely empiric treatment remain crucial to guide care despite limited diagnostic resources. Conclusion: Pediatric liver abscess can still be effectively managed in low-resource settings through prompt diagnosis, empiric therapy, and timely surgical intervention.